Optimization of Water Fraction Gel Formula of Binahong Leaf (Anredera cordifolia (Ten.) Steen) With Gelling Agent of Sodium Alginate and Carboxymethyl Chitosan Combination - Citra Ariani Edityaningrum; Kintoko Kintoko; Feby Zulien; Lina Widiyastuti (Faculty of Pharmacy, Universitas Gadjah Mada, 2018)
Water fraction of binahong (Anredera cordifolia (Ten.) Steen) leaf has been proven to heal ulcus diabetic. In order to make the use easier and more practical, in this study the water fraction of binahong leaves is formulated in gel preparation form. This study was conducted to obtain a comparison of the amount of sodium alginate and carboxymethyl chitosan as gelling agent to produce gel that meets the good physical requirements. The method used to determine the amount of comparison of sodium alginate and carboxymethyl chitosan is to use Simplex Lattice Design (SLD). Eight variations of gel formula are designed with the ratio of sodium alginate: carboxymethyl chitosan as follows: F1 (0:3% w/w), F2 (0:3% w/w), F3 (0.75:2.25% w/w), F4 (1.5:1.5 % w/w), F5 (1.5:1.5% w/w), F6 (2.25:0.75% w/w), F7 (3:0% w/w), F8 (3:0% w/w). Physical parameters observed included pH, viscosity, dispersion, and adherence. Data obtained compared with the actual conducted by researchers using one sample test t-test with 95% confidence level. Based on the results of the study, increased sodium alginate concentration can increase viscosity and adhesiveness and decrease the pH and spreadability of the gel. One sample t-test analysis shows that there is no significant difference between predicted parameter value and actual result so SLD equation can be used to construct gel formula of water fraction of binahong leaf. The conclusion is a combination of sodium alginate 1.546% w/w and carboxymethyl chitosan 1.454% w/w yield gel optimum. Physical parameter response of optimum formula is pH 5.86; viscosity 2000 cps; spreadability of 21,96 cm2; and adhesiveness of 19,81 seconds.